Architecture of tourist and leisure facilities on the Kłodzko-Orlice borderland, on the example of Zieleniec and Lasówka - Suchodolski, Jacek (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2018)
On the Kłodzko-Orlice borderland on the Dzika Orlica river, regional architecture had a great influence on the form and character of the tourist and recreation facilities built there until 1945. After the Second World War many of these buildings ceased to exist. The new ones do not refer to the rich heritage of the region, as evidenced by the architecture and construction details of guest houses, holiday homes, villas or inns in Zieleniec and Lasówka the best developing locations of the region today, but largely devoid of regional character.